ANALYSIS OF FATIGUE RISK FACTORS ON WORKERS IN X TOFU FACTORY, SEMARANG - Zakaria, Amirul Afif; Lestantyo, Daru; Jayanti, Siswi (Jurnal Kesehatan Masyarakat, 2024)
Fatigue is a condition where there is a decrease in the capacity or performance of workers who usually appears with feelings of weakness caused by physical and psychological factors. Fatigue in Tofu X factory workers can lead to decreased productivity and/or preparedness which can result in work accidents. The purpose of this study was to analyze work fatigue and the factors that influence work fatigue at Tofu X factory. The data collection process was carried out from November to December 2022, data was taken from 10 (ten) informants (workers). This study used a descriptive qualitative design with observation and in-depth interviews to obtain the characteristics of the informants, physical workload, length of service, and hot work climate. The results of the study showed that workers with a mild underweight nutritional status had the highest fatigue scores compared to normal nutritional status and mildly obese nutritional status. Workers with the female gender, even though they have a lighter workload, still experience work fatigue. Work fatigue in workers with the shortest tenure has a higher fatigue score compared to workers with long tenure. The physical workload felt by workers based on measurements of the working pulse is quite heavy so that complaints arise from workers. Measurements of the hot working climate show that several soybean processing posts have a Wet Bulb Globe Temperature Index above the Threshold Value. Workers experience medium category work fatigue, and symptoms of fatigue are felt in the form of complaints such as dizziness, weakness, aches in several parts of the body, and difficulty controlling emotions